Socio-Economic Factors Influencing Solid Waste Management in Urban Centres of Nandi County - James Meli; Sumukwo Joel; Kiplimo Lagat, (African Journal of Education,Science and Technology (AJEST), 2025)
Rapid population growth, urbanization, industrialization and economic development have resulted in the generation of big volumes of solid waste in Nandi County. Yet solid waste is an economic commodity that may not be optimally allocated through the market mechanism. Most attempts to solve waste problems in Kenya focus on supply-side of waste disposal and collection, which have not been successful. This study examines the following objectives: Assess the effects of education, age, and gender on management of solid waste; evaluate how household incomes influence SWM in Nandi County; examine various policy options in management of urban solid waste in Nandi County. This study is guided by utility theory which provides a valuable framework for understanding and analysing decision-making processes related to waste management practices. Data were collected through stratified sampling of 380 respondents, where interview guides and questionnaires were applied. Key findings reveal that gender and income levels are significant predictors of solid waste generation. High-income earners (KSh. 91,000–100,000 monthly) are the largest waste generators, while low-income earners (<KSh. 30,000) cumulatively generate less. Industrial and packaging-related waste accounts for 37% of corporate waste, followed by tea waste (20%) and market waste (15%), reflecting the dominance of manufacturing and agricultural trade in the region. A multiple regression analysis proved that gender, and monthly household income, collectively explained up to 50% of the variation of solid waste management. These results indicate the need for development of gender-specific strategies and policies that are oriented to income disparities, to improve solid waste management. The study recommends offering incentives for minimization of waste disposal such as waste-to-energy practices for tea companies and establishment of affordable recycling facilities for low-income households and informal sector players.